Safety of EUS latex balloon use in patients with a latex allergy - Salame, Marita; Gleeson, Ferga C.; Chandrasekhara, Vinay; Law, Ryan J.; Rajan, Elizabeth; Iyer, Prasad G.; Bofill-Garcia, Aliana; Ghanem, Omar M.; Abu Dayyeh, Barham K.; Ravi, Anupama; Storm, Andrew C.; Vargas, Eric J. (Gastrointestinal endoscopy, 2024)
Balloons are used in EUS to improve visualization. However, data on the safety of latex balloons in patients with latex allergies are limited, and nonlatex alternatives can be costly. We investigated the safety of latex balloon use during EUS. A retrospective review was conducted at a tertiary center between 2019 and 2022. Patients with reported latex allergies who underwent linear EUS were included. Baseline demographics, EUS characteristics, and adverse events were collected. The primary outcome was the rate of adverse events. Eighty-seven procedures were performed on 57 unique patients (mean age, 65.3 ± 14.5 years). Latex balloons were used in 59 procedures (67.8%), with only 8 procedures (13.6%) using prophylactic medications. No adverse events occurred during or after procedures, regardless of medication use or history of anaphylaxis. The use of EUS latex balloons in patients with a latex allergy was associated with no adverse events.